Contraceptive Risk : The FDA, Depo-Provera, and the Politics of Experimental Medicine - Green, William, 1950- (Book collections on Project MUSE., 2017)
Depo-Provera is known as an injectable hormonal birth control method, but few are familiar with its dark and complicated history. Depo-Provera was tested on women since the mid-1960s without their informed consent until it was FDA-approved in 1992, but never FDA-approved as chemical castration for male sex offenders. Contraceptive risk is the author's landmark study of Depo-Provera. Based on a fascinating combination of archival materials and interviews, the book is framed as three interconnected stories told by Judith Weisz, who chaired the FDA's Public Board of Inquiry on Depo-Provera, a scientific court; by Anne MacMurdo who brought a products liability suit against Upjohn, the drug's manufacturer, for the deleterious side effects she suffered from the drug's use; and by Roger Gauntlett, an Upjohn heir who, when he was convicted of sexual assault, refused to take a dose of his family's own medicine as a probation condition. Together these three stories of Depo-Provera's convoluted fifty year odyssey call for a paradigm shift in pharmaceutical drug development. Contraceptive risk is a thoroughly researched and engrossing approach to the scientific, political and institutional forces involved in health law and policy, as well as the multifaceted politics of measuring risk.--description from back cover.